Prostitution and violence: Evidence from Sweden - Maria Perrotta Berlin; Giovanni Immordino; Francesco Flaviano Russo; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2019)
This paper analyzes the effects of the "Nordic Model" of prostitution legislation adopted in Sweden in 1999, according to which buyers only are prosecuted. We focus on various measures of violence, distinguishing between known and unknown perpetrator, indoor and outdoor crimes, and on health outcomes such as hospitalizations. This allows us to assess whether violence occurs within the prostitution market, or outside of it, namely as domestic violence. The empirical analysis shows an increase in violence as a consequence of the criminalization of buyers, but mostly ascribable to domestic violence rather than violence towards sex workers. We propose a model that rationalizes our conclusions on the source of the increase in violence and to simulate the effects of other policies.
Keywords: L51; I18; O17; H21; 330; Prostitution; Regulation; Prohibition; Laissez-faire; Violence